Chimpanzees of the lakeshore natural history and culture at Mahale - Nishida, Toshisada, 1941-2011 (Cambridge University Press, 2012)
"Chimpanzees are humanity's closest living relations and are of enduring interest to a range of sciences, from anthropology to zoology. In the West, many know of the pioneering work of Jane Goodall, whose studies of these apes at Gombe in Tanzania are justly famous. Less well-known, but equally important, are the studies carried out by Toshisada Nishida on the eastern shore of Lake Tanganyika. Comparison between the two sites yields both notable similarities and startling contrasts. Nishida has written a comprehensive synthesis of his work on the behaviour and ecology of the chimpanzees of the Mahale Mountains. With topics ranging from individual development to population-specific behavioural patterns, it reveals the complexity of social life, from male struggles for dominant status to female travails in raising offspring. Richly illustrated, the author blends anecdotes with powerful data to explore the fascinating world of the chimpanzees of the lakeshore"--